Duplicated middle cerebral artery associated with aneurysm at M1/M2 bifurcation: a case report - Mori, Kentaro (J Med Case Rep, 2018)
BACKGROUND: A duplicated middle cerebral artery arises from the internal carotid artery and supplies blood to the middle cerebral artery territory. A duplicated middle cerebral artery is sometimes associated with an intracranial aneurysm. Most aneurysms associated with duplicated middle cerebral artery are located at the origin of the duplicated middle cerebral artery. An aneurysm located at the distal middle cerebral artery is not common. CASE PRESENTATION: We encountered a 62-year-old Asian man with duplicated middle cerebral artery associated with aneurysms at the M1/M2 junction of the duplicated middle cerebral artery and top of the internal carotid artery. CONCLUSIONS: In cases of duplicated middle cerebral artery, association with a distal aneurysm on the duplicated middle cerebral artery is rare. However, the aneurysm may be formed on the thicker middle cerebral artery due to hemodynamic stress.